Black Soldier Fly (Hermetia illucens) Microbiome and Microbe Interactions: A Scoping Review - Shu-Wei Lin; Matan Shelomi (Animals)
Black soldier fly (Hermetia illucens, BSF) is farmed worldwide to convert organic waste into usable biomaterials. Studies on the larval microbiome have been carried out to check for symbiotic or pathogenic microbes and their respective functions and fates. Some studies tested these microbes for industrial applications, while others tested the effects of exogenous microbes as probiotics or for substrate pre-processing to improve larval fitness, bioconversion rates, or nutritional qualities. This review examined all peer-reviewed literature on these topics to consolidate many disparate findings together. It followed the PRISMA guidelines for scoping reviews. The results found no evidence of globally conserved core microbes, as diet strongly correlated with gut microbiome, but some genera appeared most frequently in BSF larval guts worldwide regardless of diet. The gut microbes undoubtably assist in digestion, including pathogen suppression, and so microbial probiotics show promise for future investigations. However, the common gut microbes have not been explored as probiotics themselves, which would be a promising direction for future work. The impacts of BSF bioconversion on pathogens varied, so each rearing facility should investigate and manage their pathogen risks independently. The data summarized in this study provide useful reference points for future investigations into BSF–microbe interactions.